2019
DOI: 10.5194/aab-62-199-2019
|View full text |Cite
|
Sign up to set email alerts
|

Testing eye temperature assessed with infrared thermography to evaluate stress in meat goats raised in a semi-intensive farming system: a pilot study

Abstract: The Blanca Serrana goat is selected for meat production and usually raised in an extensive farm system. The meat goat industry is getting bigger in Spain, evolving to more intensive farming systems. The negative influence of stress produced by daily management on animal welfare is even bigger in these animals as they are not used to getting so close to humans. Eye temperature has recently appeared as an appropriate and noninvasive tool for welfare assessment in cattle, but no previous studies have been develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Under stressful conditions, Cannas and colleagues suggested that changes in temperature in the small areas present around the posterior border of the eyelid and the caruncula lacrimalis are due to changes in blood flow caused by the activation of the autonomic nervous system, because this area has rich capillary beds innervated by the sympathetic system [ 47 ]. On the other hand, Bartolomé and colleagues stated that the increase in eye temperature after a fearful stimulus could be a response associated with the activation of the hypothalamic–pituitary–adrenal axis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under stressful conditions, Cannas and colleagues suggested that changes in temperature in the small areas present around the posterior border of the eyelid and the caruncula lacrimalis are due to changes in blood flow caused by the activation of the autonomic nervous system, because this area has rich capillary beds innervated by the sympathetic system [ 47 ]. On the other hand, Bartolomé and colleagues stated that the increase in eye temperature after a fearful stimulus could be a response associated with the activation of the hypothalamic–pituitary–adrenal axis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results suggested that the unfamiliar experimenter was perceived as more threatening after the handling procedure, with the restraint having a negative impact on the human–animal relationship. In 2019, Bartolomé and colleagues [ 48 ] validated the use of IRT to analyze stress reactions in goats ( Capra aegagrus hircus ) caused by a person walking around the animals, making noise, and waving their arms to guide them to another pen. Respiratory rate and lacrimal caruncle temperature were higher after the stress test than before, and there was a positive correlation between them.…”
Section: Applicationsmentioning
confidence: 99%
“…As with the EEG responses, environmental factors likely influenced IRT results, as a similar trend was observed over time, with no treatment interaction. Changes in eye temperature have been used to indirectly measure autonomic nervous system activation in livestock including cattle [11,22] and stress inducing scenarios in goats [23] and sheep [24,25]. Stress-induced hyperthermia occurs as an initial decrease in surface temperature followed by an increase in core body temperature as a result of a stressful stimulant [26].…”
Section: Discussionmentioning
confidence: 99%
“…According to Siebert et al [ 41 ], goats do not habituate to social isolation, which implies that the generally higher heart rate at two weeks, compared to two months, was probably not a habituation effect. Adult goats have lower heart rate than goat kids [ 58 ], thus, the lower heart rate at two months may be an age effect.…”
Section: Discussionmentioning
confidence: 99%